Emerging Digital Technologies and Their Implications for Business Leaders: A Look into The Future - Munawar Javed Ahmad; Muhammad Arif (Business Review of Digital Revolution, 2022)
This article aims to provide business leaders with an overview of emerging digital technologies and their potential implications for businesses in the near future. A comprehensive review of existing literature on emerging digital technologies and their applications in business was conducted. The article also draws on expert opinions and case studies to provide practical insights into the potential impact of these technologies on businesses. The article identifies several emerging digital technologies, including artificial intelligence, blockchain, virtual and augmented reality, and the Internet of Things, and discusses their potential implications for business leaders. These implications include changes in business models, new opportunities for innovation, and the need for new skills and talent. As digital technologies continue to rapidly evolve, business leaders must be prepared to adapt and embrace these changes to remain competitive. By understanding the potential implications of emerging digital technologies, businesses can position themselves to take advantage of new opportunities and navigate the challenges of an increasingly digital world.
Keywords: Digital Adoption, R&D Investment, Organizational Learning, Business Performance.